Antidepressant utilization patterns and predictors of treatment continuation in pregnant women: A 16-year population-based cohort. (May 2023) - Hung, Chun; Chan, Joe Kwun Nam; Wong, Corine Sau Man; Fung, Vivian Shi Cheng; Lee, Krystal Chi Kei; Chang, Wing Chung
Objective: Existing data on prenatal antidepressant prescribing patterns are mostly derived from Western countries, with limited research assessing antidepressant continuation and reinitiation during pregnancy. This study aimed to examine antidepressant prescribing practice among Chinese pregnant women in Hong Kong. Methods: This population-based study identified women aged 15–50 years who delivered their first and singleton child, and had redeemed at least one antidepressant prescription within 3 months pre-pregnancy and/or during pregnancy between 2003 and 2018, using data from the health-record database of Hong Kong public healthcare services. Antidepressant utilization patterns before and during pregnancy, and factors associated with antidepressant continuation and reinitiation following medication discontinuation were evaluated. Results: Of 466, 358 pregnancies, 3019 (0.67%) received antidepressants within 3 months of pre-pregnancy and/or during pregnancy, and 2700 (0.58%) had prenatal antidepressant use. There was a significant rising trend of prenatal antidepressant use over time (0.6% in 2003 to 1.3% in 2018; odds ratio: 1.09, 95% confidence interval = [1.08, 1.10], p  < 0.001). A consistent pattern of decreasing overall antidepressant use from 3 months pre-pregnancy to the second trimester was observed, followed by a slight increase in the third trimester. Almost half ( n  = 949, 49.5%) of 1918 women on antidepressants in 3 months pre-pregnancy continued treatment beyond the first trimester. A total of 8.2% that discontinued antidepressants in 3 months pre-pregnancy or in the first trimester reinitiated treatment in the later stage of pregnancy. Older age at conception (⩾35 years), recent calendar year of delivery (2015–2018), pre-existing depression/anxiety disorders, longer-term pre-pregnancy antidepressant treatment and pre-pregnancy prescription of other psychotropics were significantly associated with antidepressant continuation. Antidepressant reinitiation was predicted by pre-existing depression/anxiety disorders. Conclusions: Our results that prenatal antidepressant use is increasingly prevalent and half of pregnant women discontinued antidepressants 3 months before or after conception underscore the need for future research to clarify the risk and benefit of antidepressant continuation versus discontinuation to facilitate development of evidence-based guidelines, so as to optimize maternal and fetal outcomes.